CANDOMBLÉ, PRÁTICAS EDUCATIVAS E AS RELAÇÕES DE GÊNERO NO ESPAÇO SOCIAL ONDE FILHAS E FILHOS DE SANTO APRENDEM E ENSINAM POR MEIO DA ORALIDADE - GALLICIANO, VANIA (2015)
The present article focuses on the educational actions, and relationship practices on the part of “Mães e Pais de Santo”, who are frequenters of the Houses of Àse, and on gender relations. Results were obtained by means of visits and interviews carried out from December, 2013 to February, 2014. During this period, the researcher spent three weeks with the House of Àse’s members. She took part in rituals, as well as on their preparation, including the initiation process of Ìyáwó. Throughout this experience formal and informal dialogues were exchanged among the houses’ members. Observations yielded unexpected answers to the questions posed. The study investigated specific institutions of the Afro-Brazilian religion through verbal reports from Pais, Mães and filhos de Santo. Methods, the teaching of culture, the doctrine and gender relations were analyzed, as well as their influence on the process of “being” and “doing” in the context of the Houses of Àse. Bearing that in mind, and given the investigative character of this study; one searched for information about the interviewed, as well as their ancestors’ religious past and origins amongst other background information.